The comparative analysis of immunohistochemical parameters of primary liver cancer and liver metastases of malignant tumors of solid, trabecular, tubular-glandular structure in puncture trephine biopsy - V. A. Tumanskiy; M. D. Zubko; V. G. Maksimenko (Patologìâ)
Aim. In puncture trephine biopsy of the liver differential immunohistochemical (IHC) parameters of hepatocellular carcinoma (HCC) in 30 patients, cholangiocellular cancer (CC) of the liver in 15 patients, and liver metastases of malignant tumors of solid, trabecular structure [melanoma (12), breast cancer (10), neuroendocrine tumors (12), prostate cancer (2)] and tubuloglandular structure [ductal carcinoma of the pancreas (12), adenocarcinoma of the stomach (10), colorectal cancer (17), RCC (6), cancer lung (4)] were studied.